A new bi-imaging NDT system for simultaneous recovery of attenuation and electronic density maps - Tarpau, Cecilia (2020)
Computed Tomography is a widely used imaging technique for non-destructive testing and evaluation in industry. Tomographic modalities exploit only primary radiation, which is non-deviated but attenuated radiation going through matter. However, in the energy range of X and gamma rays used in non destructive testing, Compton effect is an important physical phenomenon which should be taken into account. Compton Scattering Tomography is precisely theimaging technique, which not only accounts for the Compton effect but also uses it to image material electronic density. This paper proposes the concept of a Compton scanner,which is formed by a source and several detectors placed on a circular ring. When the detectors are set to register the energy of primary photons, the system works as Fan-Beam computed tomography scanner. But if the detectors are set to register the energy of scattered photons, the system operates as Compton scattering tomography scanner. Such a device, that we called a bi-imaging system provides both the attenuation map and the electronic density of the scanned object. Both information from primary and scattered rays is then wisely exploited. The mathematical modelling of this system makes use of a Radon transform on circular arcs. Numerical simulations are carried out in order to illustrate the theoretical feasibility of the proposed system.